The Influence of Plasticine Play to Develop Children's Creativity Abilities - Fitriani Fitriani; Hayana Hayana; Suryani L; Muqimah Surganingsih (Universitas Negeri Makassar, 2022)
This research aims to see how playing with plasticine activities improves children's creative abilities. The research subjects were 15 students of Idhata Pitumpidange Kindergarten. This study uses a quantitative approach, non-parametric descriptive statistical data analysis, and data collection instruments with observation sheets. The results of the research analysis have been carried out through several meetings and based on all the discussions and data analysis that have been carried out. It can be concluded that the use of playing plasticine influences increasing the ability of creativity. Playing plasticine activities can improve children's imagination, with indicators in the research being the skills to make shapes and add other conditions to existing forms. This is shown from the data analysis of Idhata Pitumpidange Kindergarten students in Group B with 15 students. The results of data analysis showed that at the time of the pretest, the creativity ability level was 40.0%, with an average value of 2.23. 90%, and the average value of students is 3.07.